Resolvemos situaciones de contexto aplicando progresiones geomtricas - Yabar Rojas, Marilu (2018)
Mathematics is a human activity and occupies a relevant place in the development of knowledge and culture of our society. Learning mathematics contributes to form citizens capable of solving problematic situations in their daily life. In the development of the learning session, several situations were presented where the student puts into practice his mathematical knowledge guided by the teacher, putting into practice what he learned in class; in his daily life and problematizing different situations that help students to understand the world around them In this learning session, we will discuss geometric progressions in which a daily situation is presented, which will help them to better understand the topic, and we will also ask questions which will help students to problematize the situation presented and so they will understand that mathematics is present in our daily life.